2015
DOI: 10.1002/ar.23157
|View full text |Cite
|
Sign up to set email alerts
|

Hyoid Bone Development: An Assessment Of Optimal CT Scanner Parameters and Three‐Dimensional Volume Rendering Techniques

Abstract: The hyoid bone anchors and supports the vocal tract. Its complex shape is best studied in three dimensions, but it is difficult to capture on computed tomography (CT) images and three-dimensional volume renderings. The goal of this study was to determine the optimal CT scanning and rendering parameters to accurately measure the growth and developmental anatomy of the hyoid and to determine whether it is feasible and necessary to use these parameters in the measurement of hyoids from in vivo CT scans. Direct li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…Additional CT scans from both typically and atypically developing individuals, such as those with Down syndrome or cerebral palsy, would permit us to better understand the nature of hyoid bone fusion across the lifespan as well as the overall trends of hyoid bone form and function during growth and development. Cotter et al [ 4 ] found that ex vivo hyoid bones taken from cadavers can be suitably compared to 3D renderings of in vivo hyoid bones created from CT scans. Additional measurements, including linear, angular and volume, of the hyoid bone from CT scans would permit us to test models that incorporate dimensions of the hyoid bone and bone density for understanding developmental trends and further refining sex and age estimation.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additional CT scans from both typically and atypically developing individuals, such as those with Down syndrome or cerebral palsy, would permit us to better understand the nature of hyoid bone fusion across the lifespan as well as the overall trends of hyoid bone form and function during growth and development. Cotter et al [ 4 ] found that ex vivo hyoid bones taken from cadavers can be suitably compared to 3D renderings of in vivo hyoid bones created from CT scans. Additional measurements, including linear, angular and volume, of the hyoid bone from CT scans would permit us to test models that incorporate dimensions of the hyoid bone and bone density for understanding developmental trends and further refining sex and age estimation.…”
Section: Discussionmentioning
confidence: 99%
“…Intensity in Hounsfield units (HU), commonly used to measure bone density, was then calculated from the outlined region defined by the 3D model generated using the Region of Interest tool (ROI) within Analyze 11.0 ® . See Cotter et al [ 4 ] for additional detail on modeling methods. Lee et al [ 22 ], Majumdar and Leslie [ 23 ], Schreiber et al [ 24 ], and Lee et al [ 25 ] all found that intensity in Hounsfield units calculated from CT scans is a suitable estimation for bone mineral density as calculated by dual-energy X-ray absorptiometry (DXA), which remains the gold standard for bone density measurement.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The Bone and Soft algorithms were included if the Standard algorithm was not available to ensure a balance in age and sex distribution in this study. As for slice thickness, both Whyms et al (2013) and Cotter et al (2015) determined less than or equal to 2.5 mm thickness to be adequate for the reliable assessment of linear measurement of growth and development for the mandible and the hyoid bone, respectively. For additional detail, see Miller et al (2019).…”
Section: Methodsmentioning
confidence: 99%